Consumer preferences for micronutrient strategies in China. A comparison between folic acid supplementation and folate biofortification - De Steur, Hans; Feng, Shuyi; Xiaoping, Shi; Gellynck, Xavier (Public health nutrition, 2014)
Despite public health efforts, folate deficiency is still largely prevalent in poor, rural populations and continues to cause a large burden of disease. The present paper determines and compares consumer preferences for two folate strategies: folic acid supplementation v. folate biofortification, i.e. the enhancement of the folate content in staple crops. Experimental auctions with non-repeated information rounds are applied to rice in order to obtain willingness-to-pay for folate products. Thereby, GM or non-GM folate-biofortified rice (FBR) is auctioned together with rice that is supplemented with free folic acid pills (FAR). Shanxi Province (China) as a high-risk region of folate deficiency. One hundred and twenty-six women of childbearing age, divided into a school (n 60) and market sample (n 66). Despite differences according to the targeted sample, a general preference for folate biofortification is observed, regardless of the applied breeding technology. Premiums vary between 33·9 % (GM FBR), 36·5 % (non-GM FBR) and 19·0 % (FAR). Zero bidding behaviour as well as the product choice question, respectively, support and validate these findings. The targeted sample, the timing of the auction, the intention to consume GM food and the responsibility for rice purchases are considered key determinants of product choice. A novel ex-post negative valuation procedure shows low consistency in zero bidding. While the low attractiveness of FAR provides an additional argument for the limited effectiveness of past folic acid supplementation programmes, the positive reactions towards GM FBR further support its potential as a possible complementary micronutrient intervention.